Alavancagem das vendas por cross-selling e up selling por meio de soluções digitais - Fagundes, Paula Lamperti (Universidade do Vale do Rio dos Sinos, 2023)
Digital transformation has erupted in recent years as a result of the COVID-19 pandemic. Online sales platforms have emerged as an alternative and have contributed to strengthening the connection beyond the physical point of sale between consumers and brands. Parallel to this, there was renewed talk of the Metaverse: a possible new channel for selling and interacting. With the intention of contributing to the improvement of knowledge related to commerce in conjunction with the Metaverse, this study's main objective is to identify the requirements to leverage sales using techniques already well consolidated in the market – cross-selling and upselling – in fashion items (clothing and footwear), through digital solutions and immersive technologies, which are delimited in the scope of the Metaverse. The research also presents knowledge gaps, indicated by retail and technology experts. The results of the study contribute to enable better experiences by pointing out what is needed to connect different digital solutions that can facilitate immersion in virtual environments.
Keywords: Metaverso; Varejo; Cross-selling; Upselling; Tecnologias digitais; Fashion; Metaverse; Retail; Digital technologies; ACCNPQ::Engenharias::Engenharia de Produção